IMAGE OF PSYCHIATRY AMONG MEDICAL COMMUNITY - Jiloha, R.C. (Medknow Publications, 1989)
Psychiatry as a medical discipline has been variously described. Even among medical community psychiatry was looked down upon as medical speciality. After World War II when psychiatry's importance was realized for total treatment, its image was supposed to have improved. In the light of these ups and downs a survey of medical community consisting of 5000 doctors was conducted results of which reveal that the role of psychiatry is favourable. Respondent's comments and criticism were constructive and consistent. Important facts highlighted by this survey are that the undergraduate training in psychiatry is inadequate and the general public carries a frightening image about psychiatry according to the medical men. Therefore, it is suggested that medicos need more exposure to psychiatry and undergraduate training in psychiatry needs to be revised.